Rheo-optical characterization of liquid crystalline acetoxypropylcellulose melt undergoing large shear flow and relaxation after flow cessation - Teixeira, Paulo F. (2016)
The rheological and structural characteristics of acetoxypropylcellulose (APC) nematic melt are studied at shear rates ranging from 10 s(-1) to 1000 s(-1) which are relevant to extrusion based processes. APC shows a monotonic shear thinning behavior over the range of shear rates tested. The negative extrudate-swell shows a minimum when a critical shear rate (gamma) over dot(c) is reached. For shear rates smaller than (gamma) over dot(c), the flow-induced texture consists of two set of bands aligned parallel and normal to the flow direction. At shear rates larger than (gamma) over dot(c), the flow induced texture is reminiscent of a 2 fluids structure. Close to the shearing walls, domains elongated along the flow direction and stacked along the vorticity are imaged with POM, whereas SALS patterns indicate that the bulk of the sheared APC is made of elliptical domains oriented along the vorticity. No full nematic alignment is achieved at the largest shear rate tested. Below (gamma) over dot(c), the stress relaxation is described by a stretched exponential. Above (gamma) over dot(c), the stress relaxation is described by a fast and a slow process. The latter coincides with the growth of normal bands thicknesses, as the APC texture after flow cessation consists of two types of bands with parallel and normal orientations relative to the flow direction. Both bands thicknesses do not depend on the applied shear rate, in contrast to their orientation. (C) 2015 Elsevier Ltd. All rights reserved.